Pembentukan Portofolio Optimal Pada Saham-Saham Jakarta Islamic Index (Jii) Dengan Menggunakan Model Indeks Tunggal Di Bursa Efek Indonesia (Bei) Tahun 2014 - Tana, Mentari Andhis; , Dra. Wafiatun Mukharomah, MM (2016)
This research is a quantitative nature that aims to determine the optimal portfolio formation. Where the study used was the Jakarta Islamic Index (JII) with a period of 2014 samples are 28 companies listed in JII and also uses models Single Index. This formation is based on the steps looking for the return and risk of individual shares of each company and its portfolio, then calculate the optimal portfolio gains and the latter calculates the optimal return of each company. Results are from the 28 companies listed in JII 2014, formed the optimal portfolio of 11 companies with ASII code, BSDE, CPIN, INTP, JSMR, KLBF, LPKR, PGN, SMGR, SMRA, and TLKM. This analysis is based on the value of E (RB) is greater than Ci (E (RB)> Ci) can be said of the company to form the optimal portfolio. In the 11 companies that make up the optimal portfolio also turned out to form a return optimal so it can be concluded that the 11 companies that expressed in return and optimal portfolio can give you an idea that the investor when to invest their capital in order to have return optimal or expected rate of return on the 11 companies that expressed in return and the optimal portfolio. Keywords : Risk, Return, Portofolio Optimal, and Return Optimal.